Analysis of the Russian Federation Policy with relation to the Republic of Belarus (2019-2024) - Yuri Jaroschevsky (Global Labour University - Freunde und Förderer e.V., 2024)
[Introduction:] This analysis is an overview of the main areas within the relationship between the Russian Federation and the Republic of Belarus. It touches upon such aspects of the ties between the two countries as the political and economic integration, the interaction of their military, security and law enforcement forces, as well as issues related to the public opinion on these processes. The aim of this exercise is to provide a brief yet substantive overview of the key reasons behind the current state of relations, close yet quite unequal, between the two countries. A particular attention has been accorded to the process of transformation of the once multi-vector Belarusian policy into a subordinate partnership with Russia, the changes accompanying this process, as well as the reasons that have produced the dramatically substantial inequality between the two parties, inequality that cannot be explained exclusively by objective factors. The objectives of the research have emerged as, firstly, an overview of the historical events that had predestined the rapprochement of the two States; secondly, an analysis of the legal and institutional forms of the integration process, thirdly, the identification of those factors and events that strongly affected or significantly altered the relationship between the two countries, and, finally, the identification of the steps, both implemented and still remaining on paper, towards the gradually overwhelming subordination of the Belarusian State to the Russian geopolitical regional project. (...)
Keywords: 330; Außenpolitik; Russisch; Russland; Belarus